FAQ frequently ask questions - Sheikh Yusuf Estes; One Islam Production; ICRA Youth Centre, Inc.; Saba Islamic Media ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
The speaker, Sheikh Yusuf Estes answered the frequently asked question by muslim and non-muslim on Islam. This program is a short talk by Sheikh Yusuf Estes plus a QA session
Speaker: Sheikh Yusuf Estes
Keywords: Islam; Religious life -- Islam; Islam -- Essence, genius, nature